ANGGUR TUA DI LADANG LEMBEAN: Formasi Berkelanjutan dalam Kompetensi Naratif bagi Pelayanan Lansia - P. Mutiara Andalas (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2018)
The orphanage management see urgent needs to include 'narrative competence' in staff formation for the more holistic service of the elderly. The elderly psychosocial needs require the availability of staff or support groups to hear the story of elderly life. Limitations of staff at Bethania, Lembean, North Minahasa nursing home to meet these needs provide space for support groups to fill this role temporarily. In addition to applying narrative skills in communication with the elderly, this community service becomes a privileged opportunity for the researcher who is an informal teacher in this field to deepen the 'narrative competence' of the elderly. Holistic service to the elderly in the context of the demographic revolution requires the organization of nursing homes to immediately organize sustainable formation for staff in 'narrative competence'.